Regulatory T Cells: Barriers of Immune Infiltration Into the Tumor Microenvironment - Scott, Ellen N.; Gocher, Angela M.; Workman, Creg J.; Vignali, Dario A. A. (Frontiers in Immunology, 2021)
Regulatory T cells (Tregs) are key immunosuppressive cells that promote tumor growth by hindering the effector immune response. Tregs utilize multiple suppressive mechanisms to inhibit pro-inflammatory responses within the tumor microenvironment (TME) by inhibition of effector function and immune cell migration, secretion of inhibitory cytokines, metabolic disruption and promotion of metastasis. In turn, Tregs are being targeted in the clinic either alone or in combination with other immunotherapies, in efforts to overcome the immunosuppressive TME and increase anti-tumor effects. However, it is now appreciated that Tregs not only suppress cells intratumorally via direct engagement, but also serve as key interactors in the peritumor, stroma, vasculature and lymphatics to limit anti-tumor immune responses prior to tumor infiltration. We will review the suppressive mechanisms that Tregs utilize to alter immune and non-immune cells outside and within the TME, and discuss how these mechanisms collectively allow Tregs to create and promote a physical and biological barrier, resulting in an immune-excluded or limited tumor microenvironment.